Multicentre randomised phase II study of the perioperative administration of flurbiprofen axetil in patients with non-small cell lung cancer: study protocol of the FLAX Study - Kentaro Sakamaki; Katsuya Watanabe; Tetsukan Woo; Munetaka Masuda (BMJ Open)
Introduction In patients with non-small cell lung cancer, surgical treatment with postoperative adjuvant chemotherapy is performed. However, the improvement of overall survival achieved by postoperative adjuvant chemotherapy may be insufficient in consideration of the deterioration of quality of life (QOL). Considering the relationships among surgical treatments, inflammation and carcinogenesis, non-steroidal anti-inflammatory drugs (NSAIDs) are a candidate postoperative treatment for preventing recurrence and maintaining QOL. In this study, we investigate the effects of the perioperative administration of flurbiprofen axetil on postoperative recurrence in patients with non-small cell lung cancer.Methods and analysis This study is a multicentre, parallel group, open label, randomised controlled trial. Patients clinically suspected of non-small cell lung cancer are randomly assigned to the flurbiprofen axetil group or the no-NSAIDs group. A total of 420 patients (210 per group) will be registered. The primary analysis will evaluate the treatment effect of flurbiprofen axetil on postoperative recurrence.Ethics and dissemination The study protocol was approved by the Clinical Research Review Board of Saitama Medical University in September 2019 (No. 192002) and will be approved by each institutional review board of all participating institutions before patient enrolment. This study complies with the latest version of the Declaration of Helsinki, Clinical Trial Act and related notifications. Results will be published in a peer-reviewed journal.Trial registration number Japan Registry of Clinical Trials (jRCTs031190167; Pre-results) (https://jrct.niph.go.jp/).